1997
DOI: 10.1074/jbc.272.31.19304
|View full text |Cite
|
Sign up to set email alerts
|

AP1-mediated Multidrug Resistance in Saccharomyces cerevisiae Requires FLR1 Encoding a Transporter of the Major Facilitator Superfamily

Abstract: We have isolated a Candida albicans gene that confers resistance to the azole derivative fluconazole (FCZ) when overexpressed in Saccharomyces cerevisiae. This gene encodes a protein highly homologous to S. cerevisiae yAP-1, a bZip transcription factor known to mediate cellular resistance to toxicants such as cycloheximide (CYH), 4-nitroquinoline N-oxide (4-NQO), cadmium, and hydrogen peroxide. The gene was named CAP1, for C. albicans AP-1. Cap1 and yAP-1 are functional homologues, since CAP1 expression in a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
172
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(184 citation statements)
references
References 74 publications
10
172
1
1
Order By: Relevance
“…Yap1 is constitutively localized in the nucleus in the trx1⌬/trx2⌬ mutant. GFP fluorescence was visualized in living yeast cells carrying pRS cp-GFP-YAP1 (25). Cells at exponential phase were harvested, resuspended in fresh SD medium, and treated with or without 0.2 mM H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yap1 is constitutively localized in the nucleus in the trx1⌬/trx2⌬ mutant. GFP fluorescence was visualized in living yeast cells carrying pRS cp-GFP-YAP1 (25). Cells at exponential phase were harvested, resuspended in fresh SD medium, and treated with or without 0.2 mM H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The N terminus of Yap1 contains a bZip domain, which is conserved among the AP-1 family, including mammalian Jun, Fos, and S. cerevisiae Gcn4 (23). A cysteinerich domain (CRD) at the C terminus of Yap1, containing three Cys-Ser-Glu sequence motifs, plays an important role in the control of Yap1, especially for the intracellular localization of Yap1 (25,26). In the response to oxidative stress, the localization of Yap1 changes dramatically, while the increase in the DNA binding activity is modest and the levels of Yap1 do not increase (26 -28).…”
mentioning
confidence: 99%
“…Of the 16 genes that have previously been shown to be controlled by one or more of the five transcription factors, we counted six transporters, of which four were members of the ATP-binding cassette (ABC) transporter, PDR5 (Balzi et al, 1994), PDR10 (Wolfger et al, 1997), PDR15 (Wolfger et al, 2004) SNQ2 (Servos et al, 1993), and the remaining two were member of the major facilitator superfamilies TPO1 (Tomitori et al, 1999) and FLR1 (Alarco et al, 1997). The 11 remaining genes that were identified in this search do not encode multidrug resistance transporters but have other or still unknown functions.…”
Section: Carotenoid Production Induces Expression Of Genes Involved Imentioning
confidence: 99%
“…Several studies have demonstrated that Yap1p, a b-Zip protein belonging to the yeast Yap family of transcriptional regulators (Rodrigues-Pousada et al, 2004), plays a central role in sensing and modulating gene expression in response to several forms of oxidative stress (Alarco et al, 1997;Delaunay et al, 2000;Gasch et al, 2000;Lee et al, 1999;Dumond et al, 2000;Nguyen et al, 2001;Wemmie et al, 1994;1366 T. Nevitt, J. Pereira and C. Rodrigues-Pousada Azevedo et al, 2003). Yap1p-responsive genes typically contain within their promoter region a Yap-response element (YRE-TTAC/GTAA) encoding for most cellular proteins with antioxidant function and several membrane-associated drug efflux pumps .…”
Section: Introductionmentioning
confidence: 99%